Acute high-intensity interval exercise induces greater levels of serum brain-derived neurotrophic factor in obese individuals. Issue 14 (October 2018) - Rodriguez, Alexandra L; Whitehurst, Michael; Fico, Brandon G; Dodge, Katelyn M; Ferrandi, Peter J; Pena, Gabriel; Adelman, Avraham; Huang, Chun-Jung
Obesity may attenuate the expression of brain-derived neurotrophic factor (BDNF), thereby increasing the risk of cognitive dysfunction. High-intensity interval exercise (HIIE) has been shown to be as or more effective than continuous moderate-intensity exercise (CME) in promoting the expression of BDNF in normal-weight individuals. Therefore, the primary purpose of this study was to examine whether or not acute HIIE could be utilized as a practical model to explore the BDNF response in obese versus normal-weight subjects when compared to acute CME. The potential relationship of exercise-induced BDNF with blood lactate and cortisol was also examined. Twelve male subjects (six obese and six normal-weight) participated in a counterbalanced and caloric equated experiment: HIIE (30 min, 4 intervals of 4 min at 80%–90% of VO2max with 3 min of active recovery at 50–60% VO2max ) and CME (38 min at 50%–60% VO2max ). Blood samples were collected prior to, immediately following exercise, and 1 h into recovery for measurements of serum BDNF, blood lactate, and plasma cortisol. Our results showed that the BDNF response to acute HIIE was greater than CME in obese subjects when compared to normal-weight subjects. Similarly, although acute HIIE induced greater blood lactate and plasma cortisol levels than CME, obese subjects produced less blood lactate, but no difference in cortisol than normal-weight subjects. These findings suggest that acute HIIE may be a more effective protocol to upregulate BDNF expression in an obese population, independent of increased lactate and cortisol levels. Impact statement: High-intensity interval exercise (HIIE) has been shown to be a time-efficient exercise strategy that provides similar or superior physiological benefits as traditional continuous moderate-intensity exercise (CME). Our previous study demonstrated an equivalent elevation on the BDNF response in both obese and normal-weight individuals following 30 min of acute CME. To discover a time-efficient exercise strategy to improve brain health in an obese population, the present study found that obese individuals elicit a greater level of BDNF following acute HIIE versus CME than normal-weight individuals. These findings indicate that acute HIIE may be an effective strategy to upregulate BDNF expression in obese individuals.